Blockchain and maritime supply-chain performance: dynamic capabilities perspective. (7th February 2020) - Lambourdiere, Eric; Corbin, Elsa
Abstract : Purpose: Maritime supply chains rely on electronic and paper-based processes, leading to efficiency bottlenecks. The purpose of this paper is to propose a theory for how implementing digitalization in the form of blockchain technology (BCT) can improve the efficiency and effectiveness of maritime supply chains. Design/methodology/approach: This conceptual paper is grounded in dynamic capabilities, supply-chain management and digital supply-chain theories. Relevant literature is scrutinized to explain how BCT can improve supply-chain performance. Findings: BCT mainly benefits supply-chain performance through the development of intangible capabilities, by leveraging the capabilities (resources) that maritime supply chains provide. Research limitations/implications: This framework sets an analytical basis for future empirical research on BCT and maritime supply chains. As such, it can give only indications and aid in the theory-building process. Discussion on the value and effects of BCT on maritime supply chains is ongoing. Finally, the framework focuses on the application of one information technology in managing logistics activities, rather than taking a bundling approach. Practical implications: Investments in digitalization improve the overall information sharing, coordination and visibility capabilities and performances of supply chains. Originality/value: Although literature on BCT is extensive, this framework paper is the first to link BCT with dynamics capabilities and maritime supply-chain theory and will serve as a road map for future research and practice.